2023
DOI: 10.3390/foods12112265
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Strategies for Increasing Legume Consumption: Culinary and Educational Approaches

Abstract: Legumes are nutrient-dense crops with health-promoting benefits. However, several barriers are associated with their consumption. Emerging issues including food neophobic tendencies or taboos, unclear dietary guidelines on legume consumption, health concerns, and socio-economic reasons, as well as long cooking procedures, adversely affect legume consumption frequency. Pre-treatment methods, including soaking, sprouting, and pulse electric field technology, are effective in reducing the alpha-oligosaccharides a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 146 publications
0
5
0
Order By: Relevance
“…Incorporating beetroot into vegetable spreads not only improves sensory characteristics but also aligns with the growing interest in functional foods that offer health benefits related to the antioxidant-rich composition that beetroot brings to these spreads [26]. Adding vegetables and spices improves the nutritional value of the dishes and products with legumes and enhances the taste [27]. Incorporating herbs and spices like cumin into legumes can help to reduce salt content without sacrificing the hedonic liking of low-salt legume-based mezzes [28].…”
Section: Discussionmentioning
confidence: 86%
“…Incorporating beetroot into vegetable spreads not only improves sensory characteristics but also aligns with the growing interest in functional foods that offer health benefits related to the antioxidant-rich composition that beetroot brings to these spreads [26]. Adding vegetables and spices improves the nutritional value of the dishes and products with legumes and enhances the taste [27]. Incorporating herbs and spices like cumin into legumes can help to reduce salt content without sacrificing the hedonic liking of low-salt legume-based mezzes [28].…”
Section: Discussionmentioning
confidence: 86%
“…Other studies showed that legumes would also improve plasmatic levels of LDL cholesterol and triglycerides as well as affect blood pressure and endothelial function [ 101 ]. Legumes are often being called out as potentially deleterious for human health due to their content in anti-nutrients, including protease inhibitors, lectins, phytic acid, oxalate, and saponins that may reduce the bioavailability of some nutrients; however, certain procedures, such as soaking, sprouting, or simply cooking (i.e., boiling) seem to improve their digestibility and significantly limit their anti-nutrient properties [ 102 ].…”
Section: The Mediterranean Diet In Science: the Main Features In Mode...mentioning
confidence: 99%
“…According to Doma et al ( 97 ) the main characteristics that push consumers to choose beans are nutritional value, taste/consistency and versatility in cooking. While the strongest barriers to the bean’s consumption are: (I) beans are not part of traditional diet, (II) flatulence/abdominal discomfort, (III) knowledge gap about preparation and how to include them in daily diets ( 58 , 83 , 97 ), (IV) changes in lifestyles and less time available for cooking, and (V) greater availability of affordable processed foods easily to prepare ( 98 ). In this regard, consumers in developed countries avoid home-cooking beans due to the long cooking time involved.…”
Section: Common Beans As a Key Legumementioning
confidence: 99%